Computational Peniclilin Derivative That is Resistant to Acid and Beta Laktamase Enzyme - Hari Purnomo; Intan Setyorini K (Faculty of Pharmacy, Universitas Gadjah Mada, 2017)
Penicillin is an antibiotic that is still widely used to treat infections. Some penicillin derivatives are known to have acid resistance properties such as penicillin V, ampicillin, amoxicillin and methicillin. Other penicillin derivatives have resistance to beta lactamase enzymes such as methicillin, nafsilin and cloxacillin. Computational chemistry can explain why this can occur. Groups responsible for the hydrolysis process by acids and decomposition by enzymes can be calculated elektron density, so it can be understood why derivatives that are acid resistant and others are resistant to the beta lactamase enzyme. The study was conducted by optimizing each molecule using the PM3 semi-empirical method, with a gradient of 0.01 and calculating the elektron density in the carbonyl. From the results of the study it can be concluded that the acid-resistant penicillin, elektron density of the O carbonyl amide at -0.335 in penicillin V, -0.333 in methicillin, -0.316 in ampicillin, -0.315 in amoxicillin, the four less nucleophiles than the elektron density of the O amide at Benzyl penicillin which is not acid resistant is -0,347. For penicillin which is resistant to beta laktamase, it can be concluded that the elektron density of C carbonyl lactam in nafsilin + 0.272, cloxacillin + 0.270, methicillin + 0.269 is less electrophile than penicillin which is not resistant to the beta laktamase enzyme +0.280.